2020
DOI: 10.1123/ijspp.2018-0945
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between Salivary Cortisol, Training Load, and Subjective Markers of Recovery in Elite Rugby Union Players

Abstract: Purpose: Insufficient recovery can lead to a decrease in performance and increase the risk of injury and illness. The aim of this study was to evaluate salivary cortisol as a marker of recovery in elite rugby union players. Method: Over a 10-wk preseason training period, 19 male elite rugby union players provided saliva swabs biweekly (Monday and Friday mornings). Subjective markers of recovery were collected every morning of each training day. Session rating of perceived exertion (sRPE) was taken after every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…When performing this assessment in our study with elite female basketball players, elevated cortisol levels could be observed as early as Monday, which may indicate that players did not physically recover from training or from a match from the previous weekend, since the physiological stress on the players can take up to 48 h to reduce to initial levels after a match [31,32], which coincides with the results of a recent study [26]. In addition, there was a progressive increase in cortisol levels throughout the week until Friday that could indicate an increase in physiological stress from training that week, which could add up over the course of a season that begins in September and finishes in July.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When performing this assessment in our study with elite female basketball players, elevated cortisol levels could be observed as early as Monday, which may indicate that players did not physically recover from training or from a match from the previous weekend, since the physiological stress on the players can take up to 48 h to reduce to initial levels after a match [31,32], which coincides with the results of a recent study [26]. In addition, there was a progressive increase in cortisol levels throughout the week until Friday that could indicate an increase in physiological stress from training that week, which could add up over the course of a season that begins in September and finishes in July.…”
Section: Discussionsupporting
confidence: 90%
“…Regular monitoring of salivary cortisol combined with adequate planning for training load can allow for sufficient recovery to optimize sports performance [26], recovery after exercise, and the minimizing of injuries [27]. In this sense, and also to increase the Figure 2A,B shows the dispersion of cortisol levels in each group and on each of the analyzed days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus becomes necessary to monitor the concentrations and variations of stress biomarkers after competition, allowing one to establish the demands for subsequent recovery; avoiding even greater competitive stress, overtraining, fatigue, sports injuries, related diseases, and exhaustion 32,33 . Controlling all these factors has been related to an improvement in performance 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that sRPE might be a better suited and more essential method to monitor training youths in a sport like soccer (as opposed to monitoring training adults) ( Capranica & Millard-Stafford, 2011 ). Some studies also highlighted relationships between sRPE and biochemical markers of muscle damage and chronic stress, such as creatine kinase activity and cortisol concentration ( Moreira et al, 2013 ; Caetano Júnior, Castilho & Raniero, 2017 ; Tiernan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%